Almond (Prunus dulcis) Bagasse as a Source of Bioactive Compounds with Antioxidant Properties: An In Vitro Assessment - Stevens Duarte; Almudena Puchades; Nuria Jiménez-Hernández; Ester Betoret; María José Gosalbes; Noelia Betoret (MDPI AG, 2023)
The presence of components of nutritional interest makes fresh almond bagasse an interesting by-product for obtaining functional ingredients. Stabilization through a dehydration process is an interesting option for its integral use, ensuring its conservation and management. Subsequently, it can be turned into powder, facilitating its use as an ingredient. The aim of this paper was to determine the effects of hot air drying at 60 and 70 °C and lyophilization on the release of phenolic components and antiradical capacity in in vitro gastrointestinal digestion and colonic fermentation, as well as on growing microbiota composition by applying high throughput sequencing. The novelty of this study lies in this holistic approach; considering both technological and physiological aspects related to gastrointestinal digestion and colonic fermentation will provide the best conditions for functional foods. The results obtained showed that lyophilization provides a powder with a total phenol content and antiradical capacity higher than hot air drying. Furthermore, in dehydrated samples, both in vitro digestion and colonic fermentation revealed a phenol content and anti-radical capacity superior to those existing in undigested products. In addition, after colonic fermentation, beneficial bacteria species have been identified. Obtaining powders from almond bagasse is presented as an interesting opportunity for the valorization of this by-product.